EVALUASI KINERJA SIMPANG BERSINYAL DIBUNDARAN KECIL KOTA PALANGKA RAYA - Maretina Eka Sinta; Pinto Trionaldo (Fakultas Teknik Universitas Kristen Palangka Raya, 2022)
Transportation needs will continue to increase with development urban area. If the need for transportation facilities is not matched with infrastructure (road network) then transportation problems arise. This condition occurs on the Road section at the Intersection around the Small Roundabout of the City of Palangka Raya, where the amount of volume is not balanced with the capacity of roads and intersections so that the accumulation of traffic flows and create very long queues causing traffic jams during rush hour.To support this study, a sample of traffic volume is needed, and queue with a field survey on existing conditions which was carried out on 3 the day starts on Friday, 8 July 2022, Saturday, 9 July 2022, and Sunday, 10 July 2022. This evaluation method uses the Road Capacity Manual guidelines Indonesia 1997.Characteristics on Jalan Imam Bonjol in an effort to overcome problems traffic by taking action to reset the light cycle time and increase the road space capacity or maximize the effective width of the road according to the capacity of the traffic flow by setting the intersection in order to level Accidents and delays can be minimized optimally and effectively. Performance the Small Roundabout intersection of Palangka Raya City on Friday 8 July 2022 ca seen from the capacity value of the north approach 852.2 pcu/hour, degree of saturation 1.00, queue length of 95 m (service level F). On the South approach value capacity 1436.3 pcu/hour, degree of saturation 0.46, queue length 90 m (level of service). In the Western approach, the capacity value is 825 pcu/hour, the degree of saturation is 0.46, queue length of 43 m (service level B). On the Eastern approach to the value of capacity 905.1 pcu/hour, degree of saturation 0.89, queue length 67 m (level of serviceE). Keywords: Surveys, Volumes, Queues, Capacity, Degrees of Saturation, and Intersection Characteristics.